The social management of biomedical novelty: Facilitating translation in regenerative medicine. (May 2016) - Gardner, John; Webster, Andrew
Abstract: Regenerative medicine (RM) is championed as a potential source of curative treatments for a variety of illnesses, and as a generator of economic wealth and prosperity. Alongside this optimism, however, is a sense of concern that the translation of basic science into useful RM therapies will be laboriously slow due to a range of challenges relating to live tissue handling and manufacturing, regulation, reimbursement and commissioning, and clinical adoption. This paper explores the attempts of stakeholders to overcome these innovation challenges and thus facilitate the emergence of useful RM therapies. The paper uses the notion of innovation niches as an analytical frame. Innovation niches are collectively constructed socio-technical spaces in which a novel technology can be tested and further developed, with the intention of enabling wider adoption. Drawing on primary and secondary data, we explore the motivation for, and the attempted construction of, niches in three domains which are central to the adoption of innovative technologies: the regulatory, the health economic, and the clinical. We illustrate that these niches are collectively constructed via both formal and informal initiatives, and we argue that they reflect wider socio-political trends in the social management of biomedical novelty. Highlights: Various initiatives have been launched to overcome innovation challenges in RM. Innovation niche is a useful conceptual tool for exploring these initiatives. Niches are being constructed in regulatory, health economic and clinical spheres. Some niches pose epistemic 'matters of concern' for stakeholders. RM niches reflect a socio-political trends towards proactionary approach.